2014
DOI: 10.1107/s1600536814015761
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 4-fluoro-N-[2-(4-fluorobenzoyl)hydrazine-1-carbonothioyl]benzamide

Abstract: In the title compound, C15H11F2N3O2S, the dihedral angle between the fluoro­benzene rings is 88.43 (10)° and that between the central semithiocarbazide grouping is 47.00 (11)°. The dihedral angle between the amide group and attached fluoro­benzene ring is 50.52 (11)°; the equivalent angle between the carbonyl­thio­amide group and its attached ring is 12.98 (10)°. The major twists in the mol­ecule occur about the C—N—N—C bonds [torsion angle = −138.7 (2)°] and the Car—Car—C—N (ar = aromatic) bonds [−132.0 (2)°]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Atom in molecule (AIM) results demonstrated that the N-HÁÁÁCl intramolecular hydrogen bond between the 2-Cl-phenyl ring and the amide group in the free molecule changed to an H-NÁÁÁCl interaction as a result of crystal packing [47]. The inclusion of more electronegative fluorine atoms in the benzoyl group leads to similar conformational properties and the formation of intra-molecular N-HÁÁÁF hydrogen bond is further favored [48,49].…”
Section: Conformational and Structural Propertiesmentioning
confidence: 99%
“…Atom in molecule (AIM) results demonstrated that the N-HÁÁÁCl intramolecular hydrogen bond between the 2-Cl-phenyl ring and the amide group in the free molecule changed to an H-NÁÁÁCl interaction as a result of crystal packing [47]. The inclusion of more electronegative fluorine atoms in the benzoyl group leads to similar conformational properties and the formation of intra-molecular N-HÁÁÁF hydrogen bond is further favored [48,49].…”
Section: Conformational and Structural Propertiesmentioning
confidence: 99%